Competencias digitales en docentes de educación básica primaria en tiempos de pandemia y post pandemia (2022)
The objective of this research work is to design pedagogical strategies that contribute from the process of training teachers in digital skills to improve their work performance against the paradigm of the implementation of virtual education as a result of the social isolation caused by the covid pandemic. -19. And to carry out what was initially proposed here, a knowledge base was made from the state of the art that would allow knowing the root of the problem in terms of managing digital skills so that in this way establishing the methodological route that would allow teachers to be helped. in its pedagogical work with the implementation of ICT in remote teaching processes with elementary school students, initially with the conceptual strengthening of what technological skills are. In relation to this, the present research aims to improve the digital skills of teachers and for this purpose, a research design based on the IAP (participatory action research) is established since it allows, from the diagnosis, to find the deficiencies in the management technologies, to later plan the work strategy and the subsequent execution, which in the case of this work consisted of six training workshops. Showing as a result the teamwork in a collaborative and effective way, the good aptitude of the teachers in front of the training process.